A systematic literature review on factors affecting students’ online engagement towards mathematics - Faizatul Akmal Rahim; Mohd Hafizul Azrie Othman; Norshahirah Mohamed Paid; Nurhasyimah Puade (Penerbit Universiti Kebangsaan Malaysia, 2023)
Online learning has become increasingly popular due to the recent COVID-19 pandemic. Learners are expected to learn remotely from home due to the imposed movement control order. However, a major concern pertaining to students' engagement in mathematics, a subject which is considered difficult and challenging, could be undermined by the adoption of this remote learning method. Such perception could make engagement in an online environment, an environment whereby the teacher may not be able to control students directly, difficult. Therefore, it is important to review the article related to find major findings on factors affecting the students' online engagement in mathematics for helping students and teachers adapt to the online learning environment. This study aimed to perform a systematic literature review on the factors affecting students' online engagement in mathematics and the commonly used method in studying the factors. As a result, 20 credible articles from SCOPUS, Web of Science, and ScienceDirect were retrieved using predefined eligibility criteria. The results showed that technology/platform/online teaching strategies and traits were the most important factors that affect students’ online engagement in mathematics and case study was the most common method used in studying students’ online engagement towards mathematics. Educators and other interested stakeholders should consider and incorporate these factors mentioned in this research to promote engagement in Mathematics subject. Moreover, researchers can easily identify the most effective method based on this research for future research.